Design and modeling for 3D ICs and interposers - Swaminathan, Madhavan (Hackensack, NJ : World Scientific, 2014)
3D Integration is being touted as the next semiconductor revolution. This book provides a comprehensive coverage on the design and modeling aspects of 3D integration, in particularly, focus on its electrical behavior. Looking from the perspective the silicon via (TSV) and glass via (TGV) technology, the book introduces 3D ICs and Interposers as a technology, and presents its application in numerical modeling, signal integrity, power integrity and thermal integrity. The authors underscored the potential of this technology in design exchange formats and power distribution.
Includes index.
Keywords: Three-dimensional integrated circuits